Publisher Correction: Notch1 regulates the initiation of metastasis and self-renewal of Group 3 medulloblastoma. Issue 1 (December 2018) - Kahn, Suzana; Wang, Xin; Nitta, Ryan; Gholamin, Sharareh; Theruvath, Johanna; Hutter, Gregor; Azad, Tej; Wadi, Lina; Bolin, Sara; Ramaswamy, Vijay; Esparza, Rogelio; Liu, Kun-Wei; et al.
The original version of this Article omitted Suzana A. Kahn, Siddhartha S. Mitra & Samuel H. Cheshier as jointly supervising authors. This has now been corrected in both the PDF and HTML versions of the Article.